(untitled) (Research, Society and Development, 2020)
Through an integrative review of the literature, a reflective analysis was carried out on how the national policy of permanent education is recognized by health teams, and how professionals use this tool in the matrix process in mental health. The study was carried out in the Scientific Electronic Library Online (SciELO), Scopus, PubMed and MEDLINE databases, and 117 studies were found. After applying the inclusion and exclusion criteria, six articles were selected. With the analysis of the studies, the most addressed themes were identified, being listed in three categories: Challenges and gains of permanent education in mental health matriculation, Permanent education as a mental health matriculation strategy and Strategies of permanent education and matriculation in the routine of health services. The data presented by the studies show that continuing education for matrix support in mental health is recognized by professionals as an important work tool, which provides dialogue and meetings between peers, strengthening network care. However, there are reports that it is common for these spaces to lose, over time, horizontality, which is intrinsic to these institutional organizations. In this sense, it is important that the meetings are regularly evaluated, so that the teams reflect if the spaces continue to be pulsating, because without the desire, there is no permanent education, nor enrollment in mental health..